Verstärkung (m/w/d) gesucht. Zur Geschlechtsneutralität in den gegenwärtigen deutschen Stellenanzeigen - Dargiewicz, Anna (Acta Neophilologica, 2021)
The goal of this article is to examine the issue of gender neutrality of job classifieds in contemporary German language using the results of empirical analysis of a research corpus. In light of the General Act on Equal Treatment (Allgemeines Gleichbehandlungsgesetz – AGG) adopted by German Bundestag on the 14th of August, 2006, as well as the Act Modifying the Information to be Entered into the Birth Register (Gesetz zur Änderung der in das Geburtenregister einzutragenden Angaben) of the 18th of December, 2018, there is an obligation in Germany to edit job classified in accordance with gender neutrality. The implementation of linguistic equality of the sexes in job ads in such a way that they meet the guidelines of the AGG often leads to linguistic chaos and wrong and/or confusing phrasing: a fact confirmed by the examples from the above mentioned corpus. These phenomena have a considerable impact on the readability and the aesthetic qualities of the ads, and on the possibility of understanding them both in the written form and as audio files. To some extent, they also determine the degree of success of the recruitment process. Gender neutrality in language consists in expressing both male and female genders as well as other gender-related identities. However, this has to be done in accordance with grammatical, syntactic and stylistic norms. In order to prevent the “job classified” genre of texts from being misunderstood, unclearly phrased names of jobs must be eliminated.